2016
DOI: 10.21037/jss.2016.12.13
|View full text |Cite
|
Sign up to set email alerts
|

Minimising costs in spinal surgery: is group & save testing justified in lumbar decompression surgery?

Abstract: Our findings strongly suggest that pre-operative group and save is unnecessary in lumbar microdiscectomy and laminectomy. As such, we support the abandonment of routine pre-operative group and save and post-operative blood checks, with significant cost saving effects. However, O negative blood should always be available in case of major peri-operative bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…We demonstrated that blood transfusion in the context of elective lumbar laminectomy is rare. Our findings are in keeping with existing literature, which suggests that given the low risk of transfusion for this procedure, it would be safe to discontinue preoperative type and screen (9,10). With respect to other bloodwork, it has been shown that neither preoperative blood testing, nor abnormal test results, are associated with postoperative complications (11).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We demonstrated that blood transfusion in the context of elective lumbar laminectomy is rare. Our findings are in keeping with existing literature, which suggests that given the low risk of transfusion for this procedure, it would be safe to discontinue preoperative type and screen (9,10). With respect to other bloodwork, it has been shown that neither preoperative blood testing, nor abnormal test results, are associated with postoperative complications (11).…”
Section: Discussionsupporting
confidence: 88%
“…Few studies have evaluated the utility of preoperative bloodwork for elective lumbar laminectomy. The published literature to date suggests that bloodwork may be safely disregarded (9,10). Still, these investigations have been routinely ordered for patients in our facilities.…”
Section: Original Studymentioning
confidence: 99%